Diagnostic utility of IBEX Bone Health for assessment of osteoporosis from knee radiographs - Meertens, Robert; Lopez, Ben; Gundry, Mike; Crone, Ben; Vigers, Wavell; Evans, Michelle; McWilliam, Richard; Jarvis, Sarah (Frontiers in Molecular Biosciences, 2025)
PurposeThis study reports testing of IBEX Bone Health (IBEX BH) software, applied following acquisition of knee digital radiographs (DRs). IBEX BH analyses the DR to measure areal bone mineral density (aBMD) and T-scores. This study investigates aBMD and T-score at the knee as a biomarker to identify patients at high risk of osteoporosis.MethodsA 497-participant single-centre, non-randomised, prospective study was carried out comparing a) IBEX BH, a quantitative digital radiography software device, to b) Dual-energy X-ray Absorptiometry (DXA). Participants underwent left and right knee DRs, and knee, pelvis and lumbar spine DXA scans. Analysis evaluates the efficacy of IBEX BH as a knee densitometry device, comparing performance to that of reference standard DXA at the same anatomical site. It further evaluates the area under the receiver operating characteristics curve (AUC) performance of IBEX BH in predicting osteoporosis, defined by clinical reports from hip and/or spine DXA. This is compared against DXA referral recommendations derived from National Osteoporosis Guideline Group (NOGG) guidelines, which use 10-year fracture risk calculated by the fracture risk assessment tool (FRAX) without neck of femur (NoF) aBMD.ResultsCorrelations between IBEX BH aBMD and DXA aBMD at the same anatomical sites were 0.91 (95% confidence interval (CI) [0.90, 0.93]) for the proximal tibia (PT) and 0.87 (95%CI [0.84, 0.89]) for the distal femur (DF). For the PT and DF, the AUC for IBEX BH for discriminating central osteoporosis was 0.91 (95%CI [0.87, 0.95]) and 0.88 (95%CI [0.82, 0.93]) respectively, compared to 0.93 (95%CI [0.9, 0.97]) and 0.92 (95%CI [0.88, 0.96]) for DXA. In operating point analysis, the sensitivity and specificity to central osteoporosis of PT IBEX BH T-score was 0.66 95%CI [0.50, 0.78] and 0.94 95%CI [0.89, 0.96] respectively, compared to a sensitivity and specificity of 0.66 95%CI [0.50, 0.79] and 0.69 95%CI [0.63, 0.75] respectively for NOGG referral thresholds based on FRAX without NoF aBMD.ConclusionIbex BH shows strong correlation to DXA at the same anatomical site, and superior ability to FRAX without NoF aBMD for classifying central osteoporosis. Results demonstrate the potential utility of IBEX BH as a densitometer and opportunistic osteoporosis screening tool.